Assessment of Energy Consumption Pattern and Energy Conservation Potential at Indian Airports - Malik, Kanika (Penerbit Universiti Sains Malaysia, 2017)
With the growing energy crisis, the need to conserve and manage energy resources in a responsible manner is being increasingly felt by different sectors of the economy. India’s civil aviation industry is on a high-growth trajectory. India aims to become the third-largest aviation market by 2020 and the largest by 2030. The rise in the energy needs of airports to satisfy this demand has led to great concerns about the environmental impact of the aviation industry. Long term sustainability of airports is getting more important in this scenario. As demand for air travel continues to grow, aviation’s environmental impacts need to be addressed while continuing to maximize its social and economic benefts. This paper presents the problem of high energy consumption in the aviation sector by analysing the energy consumption data of three Indian airports in the composite climatic zone of India and the imperative need to design energy effcient airports. Data was collected from energy audits, which were conducted over a period of one year. The collected information was used to perform an analysis for assessing specifc measures to reduce energy use at the passenger terminal building (PTB) and to identify possible actions for improving the airport performance.